The Influence of Work Stress and Work-Life Balance to Turnover Intention on Generation Z Working Students in Karawang Regency - Abdul Khoer Al Fadily; Yudi Kristanto; Setiawati Setiawati (Business Management, 2025)
This research is motivated by the phenomenon of the increasing number of Generation Z students who work while studying in Karawang Regency, which has given rise to new problems, especially related to work stress and life imbalance, which has the potential to increase turnover intention. This study aims to analyze the influence of work stress and work-life balance to turnover intention on Generation Z working students. A quantitative approach was used in this study with a survey method through a closed questionnaire and purposive sampling technique for 60 respondents. Data were analyzed using multiple linear regression tests with the help of SPSS. The results showed that work stress had a positive and significant effect on turnover intention, temporary work-life balance has a negative and significant effect. Simultaneously, both variables influence student workers' intention to resign. This finding contributes to the development of campus and organizational policies to create a work and academic environment that better supports the well-being of student workers.